Proficiency of ICU and ER Nurses in Performing ECG Procedure and Nursing Management in Selected Hospitals in Iligan City - Boglosa, Jr., Ulysses Ecarma; Tañahura Pates, Jerese; Sarail Tanggor, Nafiesa (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This study determined the proficiency of ICU and ER nurses in performing ECG procedure and nursing management at the basic level. A total of 66 respondents were asked to participate in the study. The respondents were ICU and ER nurses working at the Gregorio T. Lluch Memorial Hospital, Mindanao Sanitarium and Hospital, Dr. Uy Hospital Inc. and the Iligan Medical Center Hospital. A 54-items questionnaire was used as an instrument in the collection of the data. It divided into 3 parts evaluating the respondents’ knowledge on the fundamentals of ECG test including a 12-lead placement, nursing management and the basic interpretation of rhythm strips. The respondent’s profile such as age, gender, marital status, and level of education, and their work related status such as the aren of assignment, years of experience as an ICU/ER and frequency performing the test were also obtained. Confidentiality was assured of the identities of the respondents as well as the individual test results. Results revealed that the over-all total average score yielded a mean proficiency of 58.02% of the respondents who took part in the study. This was below the expected range of 75% and clearly showed the insufficiency of ICU and ER nurses on the knowledge and skill on the ECG test. Findings suggested the need of a skill enhancement program and continuing education among ICU and ER nurses to render an improved quality nursing care to patients.